Cell-penetrating peptides as part of therapeutics used in cancer research - Martin Matijass; Ines Neundorf (Elsevier, 2021)
Peptides have gained more and more interest as therapeutics for different fields of medical indications. Built up via a peptide bond from naturally occurring amino acids they stand out by their high target selectivity and good biocompatibility. However, using chemical peptide synthesis also modifications are easily introduced and offer various opportunities to fine-tune their activity spectrum. One of the main areas of the global peptide market is oncology and during the past years, many peptide therapeutics with anti-tumor activity have been reported that evoke metastasis in malignant cells or evasion of cell death. Cell-penetrating peptides (CPPs) are a particular group of bioactive peptides that can be naturally or synthetically derived and have the ability to autonomously translocate in cells and transport various cargoes with them. These versatile carriers have been widely used to deliver different kinds of therapeutic molecules, and have also found application in cancer research. Within this review we will summarize recent efforts made in this direction with a focus on the specific cancer indications for which CPP-related therapeutics have been developed and studied.